Capital structure speed of adjustment heterogeneity across zero leverage and leveraged European firms - Morais, F.; Serrasqueiro, Z.; Ramalho, J. J. S. (Research in International Business and Finance, 2022)
This paper investigates whether leveraged and zero-leverage firms pursue or not a debt target level and, if so, how fast they adjust to that target. We also investigate how the influence of firms’ debt policy on capital structure speed of adjustment (SOA) changes with different financial systems, macroeconomic conditions, financial constraints and financial flexibility levels. Using the dynamic panel fractional estimator and a sample of European listed firms for the 1995–2016 period, we find that both zero-leverage and leveraged firms actively adjust to a target debt ratio. We also find that, in general, leveraged firms display a significantly higher SOA than zero-leverage firms (27.6 % vs. 22.1 %), with only two exceptions: there are no significant differences when the analysis is restricted to financially constrained firms; and during the 2008 financial crisis zero-leverage firms adjusted significantly faster (46.8 %) than leveraged firms (25.6 %) and relative to non-crisis years (21.6 %).